Tenggelamkan!: Susi Pudjiastutiâ€™s Securitization of IUUF in Indonesia - Raharjo, Wahyu Arif (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2021)
Illegal, Unregulated and Unreported Fishing (IUUF) is not traditionally discussed in security studies, but this paper attempts to prove that the emergence of IUUF in Indonesia since 2015 has become a security concern. The slogan â€œTenggelamkanâ€ (which means â€œSink It!â€) echoed by Minister of Fisheries and Maritime Affairs of Indonesia Susi Pudjiastuti indicated the surging attention, budget allocation and the sense of emergency in Indonesiaâ€™s IUUF problem. This study utilizes Securitization theory as the main framework of analysis in investigating three direct speech acts where Minister Susi attempted to securitize this issue by convincing president Joko Widodo and general Indonesian audience. This paper concludes that minister Susi had successfully securitize IUUF in Indonesia as evident in these three events: (1) the execution of exploding and sinking the captured vessels committing IUUF, (2) the militarization of IUUF in the form of involvement of Indonesian Navy and (3) the acceptance that this particular effort by minister Susi has brought fame for her as Indonesiaâ€™s female maritime hero.